1998
DOI: 10.1103/physrevb.58.14159
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic bound states in the quarter-filled ladder systemαNaV2O5

Abstract: Raman scattering in the quarter-filled spin ladder system α ′ -NaV2O5 shows in the dimerized singlet ground state (T≤TSP =35K) an unexpected sequence of three magnetic bound states. Our results suggest that the recently proposed mapping onto an effective spin chain for T>TSP has to be given up in favor of the full topology and exchange paths of a ladder in the dimerized phase for T < TSP. As the new ground state we propose a dynamic superposition of energetically nearly degenerate dimer configurations on the l… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
25
0

Year Published

1999
1999
2010
2010

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 17 publications
2
25
0
Order By: Relevance
“…Since this compound and CaV 2 O 5 are isostructural, it was also argued that the latter should also be regarded as a (half-filled) ladder system instead of only having isolated dimers (see discussion in previous paragraph). Very recent results by Lemmens et al (1998) using Raman scattering applied to NaV 2 O 5 showed an interesting sequence of magnetic bound states at low temperatures. The importance of doping NaV 2 O 5 away from quarterfilling was remarked by Smolinski et al (1998).…”
Section: Vanadium-based Ladder Compound Cav 2 Omentioning
confidence: 99%
“…Since this compound and CaV 2 O 5 are isostructural, it was also argued that the latter should also be regarded as a (half-filled) ladder system instead of only having isolated dimers (see discussion in previous paragraph). Very recent results by Lemmens et al (1998) using Raman scattering applied to NaV 2 O 5 showed an interesting sequence of magnetic bound states at low temperatures. The importance of doping NaV 2 O 5 away from quarterfilling was remarked by Smolinski et al (1998).…”
Section: Vanadium-based Ladder Compound Cav 2 Omentioning
confidence: 99%
“…Observed FIR doublets and close frequencies in different polarizations are naturally explained by their origin from the Q-point modes folded into the zone center. Prior to analyse the temperature dependences of frequencies and widths of new modes and to discuss alternative interpretations, we note that published FIR [20,23,26,5,32] and Raman [9,21,27,28,19,39,29] data agree with each other, within the precision of measurements (typically, ±0.5 cm −1 for FIR and ±1.5 cm −1 for Raman measurements).…”
Section: Lattice Dynamics Calculationsmentioning
confidence: 99%
“…[28] communicated that the 67 cm −1 Raman line neither shifts nor splits nor even broadens in a magnetic field up to 7 T. They have attributed this line and the 107 and 134 cm −1 Raman modes to magnetic singlet bound states, on the basis of (i) the temperature dependence of the intensity, frequency shift, and linewidth, and (ii) the frequency dependence on a sample quality. All the three modes rapidly loose their intensity, soften and broaden on approaching T c from below [27,28]. It is worth mentioning that very recently two more Raman modes with similar properties have been reported (namely, 86 and 126 cm −1 modes in (ab) geometry) [29].…”
Section: B Magnetic Bound States?mentioning
confidence: 99%
“…3), and perpendicular to them (aa) as well as in crossed polarization (ab) 33 . A survey of the frequencies of the additional modes is shown in Table 2.…”
Section: B Magnetic Bound Statesmentioning
confidence: 99%